Exploring the introduction of a complex intervention in primary health care facilities in the Western Cape: A single site exploratory case study of the C²AIR² club challenge - Mphaphuli, Edzani Brenda (Health Policy and Systems Division, 2018)
Context: The Western Cape Province's Department of Health, South Africa, implemented a complex intervention aimed at changing organisational culture across health facilities in the province called the C²AIR² club challenge, in phases, starting from August 2013 and was still ongoing in 2016 at the time of the research. A group of front-line staff from each participating health facility called C²AIR² club champions were capacitated to implement the intervention in their respective facilities. This study aimed to explored the process of introduction, diffusion, adoption and implementation of the C²AIR² club challenge in one of the primary health facilities where the challenge was implemented, using a diffusion of innovation lens. Methods: We examined the process of implementing the C²AIR² club and the contextual and other factors that constrained and enabled this process. Working in one primary health care facility selected as a representative case, we explored the experiences of the champions and other staff members of the C²AIR² club. Our methods included 21 in-depth interviews, informal conversations, document review, and non-participant observation. Results: Innovation-fit, leadership, champions, adopters' characteristics, and contextual issues were the main factors that influenced the spread of the C²AIR² club. Contextual issues particularly those related to resource constraints played a central role in determining the successful spread of the complex organisational culture change intervention. Sufficiently trained champions could successfully spread the intervention without onsite external change consultants' facilitation, however this took time and caution should be taken not to evaluate implementation success too early. Involvement of not only top leadership but of all other multi-levels and multi-disciplines facilitated the spread of the intervention. Conclusions: When introducing an innovation like the C²AIR² club challenge the impact of which is not immediate neither tangible, in an organisation where there are tangible problems such as lack of working space, staff shortages and shortages in working equipment, it is important that efforts are made to address these immediate challenges and where they cannot be addressed that this is openly acknowledged by the implementers and management. If this is not considered, organisational members are likely to acknowledge the innovation as a good initiative but one that they would not actively rally around as it does not speak to their problems.